2003
DOI: 10.1161/01.res.0000056965.71699.02
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hypoxic Coronary Vasodilation and ATP-Sensitive Potassium Channel Function

Abstract: H ypoxic coronary vasodilation contributes to the maintenance of oxygen supply to the working heart during increased metabolic demand. Mechanisms of hypoxic coronary dilation have been studied extensively and differ considerably depending upon the species and experimental model. In isolated coronary vessels, several mechanisms have been implicated either alone or in combination, including release of vasodilatory factors (ie, nitric oxide, prostaglandins, and adenosine), activation of ATP-sensitive potassium (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…K ATP channels are important sensors and effecter of the metabolic status of cardiomyocytes and prominently involved in the regulation of insulin secretion [17, 18], cardioprotection [1-3] and cellular adaptation to stress, such as oxidation stress [3]. Several reports have shown the relationship between dysfunction in K ATP channel gating and diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…K ATP channels are important sensors and effecter of the metabolic status of cardiomyocytes and prominently involved in the regulation of insulin secretion [17, 18], cardioprotection [1-3] and cellular adaptation to stress, such as oxidation stress [3]. Several reports have shown the relationship between dysfunction in K ATP channel gating and diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown the relationship between dysfunction in K ATP channel gating and diabetes [17]. A previous study reported that nicorandil, a mitochondrial K ATP channel opener, protects from diabetes through inhibition of the production of ROS in the streptozotocin-treated rats [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, accumulating evidence has revealed that DM has been associated with dysfunction of the cardiovascular K ATP channels (Weintraub 2003). Hyperglycemia and DM impair vasodilation mediated by K ATP channels in human vascular smooth muscle cells (Miura et al 2003, Kinoshita et al 2004, Kinoshita et al 2006.…”
Section: Introductionmentioning
confidence: 99%